PENGARUH DUKUNGAN SOSIAL KELUARGA TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN MASYARAKAT FKIP UNIVERSITAS RIAU - Franciska, Franciska; Sumardi, Sumardi; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to analyze how strong the influence of family social support on the entrepreneurship interest among students of Community Education FKIP Riau University. This research was conducted on 68 students of the Community Education study program, FKIP University of Riau. Data was collected by distributing questionnaires to the respondents using the Simple Random Sampling technique. The technique in analyzing the data are descriptive statistics and inferential statistical analysis, which the independent variable as family social support (X).Then, the dependent variable (Y) is Entrepreneurship interest. The results of the study showed that family social support had a significant positive effect on entrepreneurship interest which had a large effect of 75.7%, because there were still 24.3% determined by other factors that were not as the part of this studyKey Words: Family Social Support, Interest in Entrepreneurship, Students